Limitation of Agricultural Practices in North 24 Parganas District of West Bengal, India - Pal, B.; Goswami, A.; Mazumder, D. (International Journal of Bio-resource and Stress Management, 2023)
Agriculture is the major source of income in rural Bengal. The present study was conducted in south-eastern part of West Bengal in India. North 24 Parganas district was selected for the study. The data were collected through personal interview with the help of pre-tested structured schedule administered on randomly selected 90 respondents during November, 2010 to January, 2011. Secondary data collected from gram panchayat, government departments were also used in the study. From each of the nine gram panchayats of Barasat-I block 10 respondents were selected randomly (total sample size 90). The data were computed and analyzed using different statistical methods like frequency distribution, percentage analysis and co-relation co-efficient. The scoring method was used following socio-economic status scale (rural) and developing schedule. From the study it was found that the capital, irrigation facility and availability of improved technology were the most important constraints in the studied block. Capital was negatively and significantly correlated with marketing, whereas irrigation facility was positively correlated with availability of improved agricultural implements.